(untitled) (Revista Iberoamericana de Bioética, 2019)
Many countries oppose to surrogacy motherhood in general or at least to the paid kind, allegedly because such procedures could cause indignity to the pregnant woman. Considering the Indian experience – which is highly criticized in light of extremely degrading events – this study aims to explore whether treating the relationship between the woman and the recipients as a legal business (and the associated legal framework) could work as a solution to avoid such situations. Therefore, this study aims to demonstrate that indignity is not related to surrogacy itself, but to the conditions in which it takes place.